Conceptualizing luxury brand attachment - Shimul, Anwar (2015)
This paper aims to conceptualize luxury brand attachment and develop a scale for measuring the intensity of the attachment. A research model has been proposed with an agenda of nine hypotheses to investigate the antecedents and outcomes of the luxury brand attachment. Consumer’s self-congruity theory forms the theoretical underpinning of the research. An experimental research method will be employed to test the model and measurement scale. It will fulfil an existing gap in the luxury brand attachment construct. The findings of this paper will also provide insights for marketing managers for developing brand reinforcement and revitalization strategies for luxury brands.